2012
DOI: 10.1002/jms.3099
|View full text |Cite
|
Sign up to set email alerts
|

Reaction pathways of Sc+ (3D, 1D) and Fe+ (6D, 4F) with acetone in the gas phase: metal ion oxidation and acetone deethanization

Abstract: The reactions of Sc(+) ((3)D, (1)D) and Fe(+) ((6)D, (4)F) with acetone have been investigated in both high- and low-spin states using density functional theory. Our calculations have indicated that oxidation of Sc(+) by acetone can take place by (1) metal-mediated H migration, (2) direct methyl-H shift and/or (3) C=O insertion. The most energetically favorable pathway is metal-mediated H migration followed by intramolecular ScO(+) rotation and dissociation. For the deethanization of acetone mediated by Fe(+),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
(106 reference statements)
0
1
0
Order By: Relevance
“…On the contrary, transition metal ions with high oxygen affinities react with acetone to form MO + ions and C 3 H 6 , e.g. Sc + , V + , Ti + , Gd + and Pr + [21], [22]. The reactions of transition metal ions with acetaldehyde found that decarbonylation of acetaldehyde by Fe + , Co + , Cr + , Ni + is a dominant process at low reaction energies.…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, transition metal ions with high oxygen affinities react with acetone to form MO + ions and C 3 H 6 , e.g. Sc + , V + , Ti + , Gd + and Pr + [21], [22]. The reactions of transition metal ions with acetaldehyde found that decarbonylation of acetaldehyde by Fe + , Co + , Cr + , Ni + is a dominant process at low reaction energies.…”
Section: Introductionmentioning
confidence: 99%